The Effect of Using Zoom Conference System on Students’ Speaking Skills - Wahyudi Daud; Asri Nofa Rama (Jurnal Ilmiah Dikdaya, 2021)
he objective of this study is to investigate the effects of using zoom conference system on students’ speaking skill. This research is classified into pre-experimental research that uses one group pre-test and post-test. In the one group pre-test and post-test design, a single group is measured or observed not only after being treatment, but also before the treatment. The data of this research analyzed by using Statistical Package for the Social Science (SPSS, version 24.0) where the data of this study include quantitative data, namely students speaking skill on pre-test and post-test. Therefore, the data are analyzed by using descriptive statistic, while to test the hypothesis, the researcher used Paired Sample t-test to draw the conclusion whether or not it is accepted. The finding revealed that Zoom conferencing strategy has a noteworthy impact on students’ Speaking Skill. The probability value (p value) is less than the level of significant which p value is 0.000 < 0.05 (alpha value). Means, there is difference mean score on pre-test and post-test in experimental class.